ANALYSIS OF DUPLEX CARTONS QUALITY AVAILABLE IN THE MARKET - Mawan Nugraha; Nazula Nurul Zahra; Ponadi Ponadi (Kreator, 2021)
350-gram duplex cartons is a popular packaging material used by entrepreneurs because it is affordable, recyclable, and harmless to humans. The two main manufacturers that provide these packaged products are found in the market. In order to assist the government in providing quality assurance for consumers, the packaging materials are physically tested in accordance with SNI 10123: 2008. The quality testings include the grammature of cardboard, thickness, brightness, water absorption, oil absorption, pulling power of paper/cardboard, water content, paperboard folds, and mass density of paper/cardboard, by means of tests that have been provided by the National Standar Nasional. Indonesia (SNI). The results showed that one of the manufacturers did not meet the requirements for the brightness, while the other manufacturer did not meet the standards for the water absorption.Keywords—Resistance, Paper, Mattpaper